Guinea Pig Kisspeptin Neurons Are Depolarized by Leptin via Activation of TRPC Channels - Qiu, Jian (Endocrine Society, 2011)
Hypothalamic kisspeptin neurons are critical for driving reproductive function, but virtually nothing is known about their endogenous electrophysiological properties and the effects of leptin on their excitability. Therefore, we used the slice preparation from female guinea pigs to study the endogenous conductances and the effects of leptin on kisspeptin neurons. We targeted the arcuate kisspeptin neurons using visualized-patch whole-cell recording and identified kisspeptin neurons using immuocytochemical staining for kisspeptin or single cell RT-PCR. We also harvested dispersed arcuate neurons for analysis of expression of channel transcripts. Kisspeptin neurons exhibited a relatively negative resting membrane potential, and eighty percent of the neurons expressed a pacemaker current (h-current) and a T-type Ca(2+) current. Furthermore, the glutamate receptor agonist N-methyl D-aspartic acid depolarized and induced burst firing in kisspeptin neurons. Leptin activated an inward current that depolarized kisspeptin neurons and increased (burst) firing, but leptin hyperpolarized NPY neurons. Lanthanum, a TRPC-4,-5 channel activator, potentiated the leptin-induced inward current by 170%. The leptin-activated current reversed near −15 mV and was abrogated by the relatively selective TRPC channel blocker 2-APB. The leptin effects were also blocked by a Janus kinase inhibitor, a phosphatidylinositol 3 kinase inhibitor, and a phospholipase Cγ inhibitor. In addition, the majority of these neurons expressed TRPC1 and -5 and phospholipase Cγ1 based on single cell RT-PCR. Therefore, guinea pig kisspeptin neurons express endogenous pacemaker currents, and leptin excites these neurons via activation of TRPC channels. The leptin excitatory effects on kisspeptin neurons may be critical for governing the excitatory drive to GnRH neurons during different nutritional states.